Citizen Resistance Through Public Interest Litigation In Contemporary China - Jiang, Junxin (fi=Turun yliopisto|en=University of Turku|, 2017)
Over the past three decades, the rapid economic development at the expense of environment, social justice and civil rights has led to increasing popular contention in contemporary China. Public Interest Litigation (PIL) that emerged in the mid-1990s is part of this picture in which Chinese citizens are making use of the law and judicial process to resist rights violations caused mostly by the government and vested interests, as well as to make their voices heard. Thus, it has become a noteworthy social and legal phenomenon. The research employs the concept of rightful resistance developed by the political scientist Kevin O’Brien to explore the connection between this type of legal action and citizen resistance by placing PIL in the interaction between the state and civil society. It argues that PIL, as an idea and a litigation instrument based on rights protection and social justice, is a form of citizen resistance against the state from civil society in a posttotalitarian setting. The study examines a wide range of social, legal and political factors contributing to PIL, which include the growing public demand for social justice, a relatively workable legal framework, the increasingly raised legal and rights consciousness among the Chinese populace, and the compromise between preserving social stability by the authorities and striving for legitimate rights by civil society. It finds that PIL has attracted widespread citizen involvement with urbanites at the forefront, which is a clear indication that Chinese citizens have become more conscious of their rights laid down in laws and are courageous to stand up for them. The research discusses some non-confrontational strategies adopted by PIL practitioners, arguing that it is this moderate nature and flexibility that PIL proponents have created more social spaces for rights claim. It also provides an analysis of how concerned parties in PIL including plaintiffs, defendants, judges and the media interact to define their spaces and sometimes seek a compromise. The study emphasizes that PIL has made considerable achievements in terms of increasing public awareness of constitutional rights, contributing to reshaping the state-society relations, encouraging legal struggle to advance rights, and serving to strengthen a fledgling civil society in China. This is an interdisciplinary research based on case studies and interviews by adopting both quantitative and qualitative approaches. The study contributes to literature in the field of PIL mainly in two aspects. First, it illuminates a grey zone between citizen obedience and citizen resistance by explicitly arguing that PIL is a form of citizen resistance in the restrictive political and legal environment that has not been fully discussed in academia so far. This will be helpful to comprehend the underlying causes of this citizen legal action. Second, it examines the dynamic interaction between concerned social actors in PIL, which is conducive to enhancing the understanding of the state-society relations from a specific perspective in present-day China.

Viimeisten kolmen vuosikymmenen aikana nopea taloudellinen kehitys ympäristön, sosiaalisen oikeudenmukaisuuden ja kansalaisoikeuksien kustannuksella on lisännyt kansalaisten tyytymättömyyttä Kiinassa. Osa tätä kehitystä ovat olleet 1990-luvun puolivälistä alkaen yleisen edun nimissä käydyt oikeusmenettelyt (Public Interest Litigation, PIL), joiden kautta kansalaiset Kiinassa pyrkivät puolustamaan oikeuksiaan hallituksen ja omaa etuaan ajavien tahojen loukkauksilta sekä saamaan äänensä kuuluviin. Tästä on kehittynyt merkittävä yhteiskunnallinen ja oikeudellinen ilmiö. Tässä tutkimuksessa näiden oikeusmenettelyjen ja kansalaisvastarinnan välistä yhteyttä tutkitaan laillisen vastarinnan käsitteen kautta tarkastelemalla PIL-menettelyjä osana valtion ja kansalaisyhteiskunnan vuorovaikutusta. Tutkimuksessa esitetään, että PIL-menettely käsitteenä ja oikeuksien puolustamiseen sekä sosiaaliseen oikeudenmukaisuuteen pohjaavana oikeudellisena välineenä on kansalaisyhteiskunnan valtiota vastaan kohdistama kansalaisvastarinnan muoto jälkitotalitaarisessa yhteiskunnassa. Tutkimuksessa tarkastellaan monenlaisia PIL-menettelyyn vaikuttavia sosiaalisia, oikeudellisia ja poliittisia tekijöitä, joihin lukeutuvat kasvavat vaatimukset sosiaalisesta oikeudenmukaisuudesta, suhteellisen toimiva oikeudellinen kehys, kasvava tietoisuus oikeudellisista ja oikeuksiin liittyvistä seikoista sekä kompromissit, jotka syntyvät viranomaisten halusta säilyttää yhteiskunnan vakaus kansalaisyhteiskunnan puolustaessa oikeuksiaan. Tutkimus osoittaa, että kansalaiset ovat hyödyntäneet PIL-menettelyä laajasti, ja etenkin kaupunkilaiset ovat olleet tässä aktiivisia. Tämä on selvä osoitus siitä, että kiinalaiset ovat aiempaa paremmin tietoisia laillisista oikeuksistaan ja ovat nousseet puolustamaan niitä. Tutkimuksessa käsitellään myös joitain PIL-menettelyyn ryhtyvien kansalaisten käyttämiä maltillisia strategioita ja joustavuutta oikeusmenettelyssä ja todetaan, että nämä saattavat olla syynä siihen, miksi valtio tällä hetkellä sallii PIL-menettelyt. Tutkimuksessa korostetaan, että PIL-menettelyt ovat auttaneet merkittävästi lisäämään yleistä tietoutta perustuslaillisista oikeuksista, muokanneet valtion ja yhteiskunnan välisiä suhteita, rohkaisseet oikeuksien puolustamista oikeusteitse ja vahvistaneet orastavaa kansalaisyhteiskuntaa. Tämä on tapaustutkimuksiin ja haastatteluihin perustuva monitieteinen tutkimus, jossa käytetään sekä määrällisiä että laadullisia menetelmiä. Se laajentaa olemassa olevaatutkimusta pääosin kahdella tavalla: ensinnäkin tutkimuksessa esitetään yksiselitteisesti, että PIL-menettely on eräänlainen kansalaisvastarinnan muoto, jota akateemisessa tutkimuksessa ei ole seikkaperäisesti tarkasteltu, ja toiseksi tutkimus lisää ymmärrystä valtion ja yhteiskunnan suhteista nykypäivän Kiinassa.